If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 + -4x = 8 Reorder the terms: 7 + 5x + -4x = 8 Combine like terms: 5x + -4x = 1x 7 + 1x = 8 Solving 7 + 1x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1x = 8 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 8 + -7 1x = 8 + -7 Combine like terms: 8 + -7 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| 3m-9+-1=24 | | 2x^2-9=x^2 | | 7=-2(3y-5) | | 6(6x-7)=-86 | | 12x^2-42x+8=0 | | m+3+1=7 | | U^2+5uv+6v^2=0 | | 2x/3+x/2=7 | | 5x^2+3=0 | | 2*(x+5)=3*(2x-7)+15 | | 0.26(2.39x-4.91)=10.64 | | 8x+5+7-2x=q | | 4--4y+3y=1 | | (2x+8)(x)=2170 | | X^3-9x^2+22x-14=0 | | 31-2h/(-7)=-9 | | x+3=2x-9 | | (180-x)-(90-x)=90 | | 3(x-5)+1=34 | | 4A+10= | | -8=y-1/0-(-2) | | 3(y+8)=5y+4 | | -x+7=0 | | 324h^10-361w^2=0 | | -(-5-6n)=4(5n+3) | | 5(x+2)=3x | | 7y=1 | | 2(7x+8)=-5 | | 4-7y=1 | | 13-7x=8x+21 | | -49+10x=14+7x | | a+b(c)=a+(c)b |